Islamic Bank Safety Net Issues: The Regulatory Challenges For Cross Border Islamic Banking Transactions - Abul Bashar Bhuiyan; Abdul Ghafar Ismail; K. M. Anwarul Islam; Abd Halim Mohd Noor; Mohammad Solaiman; Mohammad Abdur Rahman (Centre for Research on Islamic Banking & Finance and Business, 2024)
Non-Indexed Publication